Salt intake among women in an Urban resettlement colony of Delhi - P Aparna; Harshal Ramesh Salve; Anand Krishnan; Lakshmy Ramakrishnan; Sanjeev Kumar Gupta; Baridalyne Nongkynrih (Wolters Kluwer Medknow Publications, 2020)
Background: Monitoring of population salt intake is essential for compliance with the WHO target of a 30% relative reduction in mean population salt intake. Objective: This study was conducted to estimate the daily salt intake and find the associated variables among adult women in an urban resettlement colony of Delhi. Methods: In this community-based cross-sectional study, 426 women aged 20-59 years from an urban resettlement colony were randomly selected. Sociodemographic details, anthropometric measurements, blood pressure, and morning spot urine samples were obtained. INTERSALT equation was used to estimate the 24-h salt intake from spot urine sodium. Association of salt intake with related variables was studied using t-test/analysis of variance, and P < 0.05 was considered to be significant. Results: A total of 426 women participated in the study, and 381 participants' urine samples could be collected. The study participants' mean age (standard deviation [SD]) was 34.5 (9.4) years. The mean salt intake (SD, 95% confidence interval) of the participants calculated using the INTERSALT equation was 7.6 (1.7, 7.5-7.8) g/day. The salt intake was significantly associated with educational status, occupation, marital status, socioeconomic status, blood pressure, and waist circumference. Waist circumference was found to have a significant positive linear relationship with daily salt intake. Conclusion: The daily salt intake of this population was well above the recommendation and had a positive linear relationship with waist circumference. Reduction in daily salt intake is a must to control the epidemic of hypertension.